1990
DOI: 10.1111/j.1365-2125.1990.tb05452.x
|View full text |Cite
|
Sign up to set email alerts
|

Leukotrienes in the sputum and urine of cystic fibrosis children.

Abstract: 1 Leukotrienes (LTs) are potent pro-inflammatory mediators with actions relevant to the pathophysiology of cystic fibrosis (CF), including increased mucus production, bronchoconstriction, leucocyte chemotaxis, and increased vascular permeability. We have therefore investigated the potential role of LTs in children with CF. Leukotriene E4 levels were assessed in the urine of 30 normal (N) children (aged 1.3-12.7 years) and 30 CF children (1.6-14.3 years). Sputum from 13 of the CF children was analysed from LTB4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
1
1

Year Published

1992
1992
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(34 citation statements)
references
References 26 publications
(25 reference statements)
1
31
1
1
Order By: Relevance
“…The levels of LTE 4 excreted in these premature infants are much higher than levels reported in normal children aged 1-13 yrs (88.4 (71.3-111) pmol·mmol -1 creatinine) [21]. This may be explained, in part, by the tendency for creatinine levels to be lower in the urine of infants (4.0 (1.3-10.5) mmol·L -1 ) than older children (10.5 (1.7-34) mmol·L -1 ).…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…The levels of LTE 4 excreted in these premature infants are much higher than levels reported in normal children aged 1-13 yrs (88.4 (71.3-111) pmol·mmol -1 creatinine) [21]. This may be explained, in part, by the tendency for creatinine levels to be lower in the urine of infants (4.0 (1.3-10.5) mmol·L -1 ) than older children (10.5 (1.7-34) mmol·L -1 ).…”
Section: Discussioncontrasting
confidence: 57%
“…Previous studies in asthmatic and normal adults (TAYLOR et al [22], 1989), and cystic fibrosis and normal children (SAMPSON et al [21], 1990) have shown urinary LTE 4 levels to be log 10 normally distributed by normal probability score (Minitab). Therefore, an unpaired Student's t-test was used on log 10 normalized urinary LTE 4 values for each group, with the results expressed as the geometric mean (95% confidence intervals (95% CI)).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…AA is a precursor of bioactive oxygenated metabolites known as eicosanoids, which include prostaglandins and leukotrienes. Production of these metabolites is known to be increased in CF, and several studies have drawn a connection between eicosanoid alterations and disease pathogenesis (54)(55)(56)(57)(58)(59). It is plausible that the observed benefi t of n-3 fatty acid therapy in the CF mouse model ( 6 ) and in a small subset of human trials ( 29,30 ) is due to its ability to normalize AA levels and, consequently, reduce excessive production of eicosanoids.…”
Section: Discussionmentioning
confidence: 99%
“…For example, cysteinyl LTs have been found in the sputum and urine of patients with cystic fibrosis (CF) (Sampson et al, 1990;Spencer et al, 1992), a disease in which the inflammatory process contributes to progressive lung tissue damage, and their concentrations increase during disease exacerbations together with oxidative stress (Reid et al, 2007). Few studies have been conducted to test the hypothesis that LTRAs have the potential to ameliorate CF lung disease.…”
Section: Cyslt In Other Diseasesmentioning
confidence: 99%